Macroporous Dual-compartment Hydrogels for Minimally Invasive Transplantation of Primary Human Hepatocytes. Issue 9 (September 2018) - Seale, Nailah; Ramaswamy, Suvasini; Shih, Yu-Ru; Verma, Inder; Varghese, Shyni
Abstract : Background: Given the shortage of available organs for whole or partial liver transplantation, hepatocyte cell transplantation has long been considered a potential strategy to treat patients suffering from various liver diseases. Some of the earliest approaches that attempted to deliver hepatocytes via portal vein or spleen achieved little success due to poor engraftment. More recent efforts include transplantation of cell sheets or thin hepatocyte-laden synthetic hydrogels. However, these implants must remain sufficiently thin to ensure that nutrients can diffuse into the implant. Methods: To circumvent these limitations, we investigated the use of a vascularizable dual-compartment hydrogel system for minimally invasive transplantation of primary hepatocytes. The dual-compartment system features a macroporous outer polyethylene glycol diacrylate/hyaluronic acid methacrylate hydrogel compartment for seeding supportive cells and facilitating host cell infiltration and vascularization and a hollow inner core to house the primary human hepatocytes. Results: We show that the subcutaneous implantation of these cell-loaded devices in NOD/SCID mice facilitated vascular formation while supporting viability of the transplanted cells. Furthermore, the presence of human serum albumin in peripheral blood and the immunostaining of excised implants indicated that the hepatocytes maintained function in vivo for at least 1 month, the longest assayed time point. Conclusions: Cell transplantation devices that assist the anastomosis of grafts with the host can be potentially used as a minimally invasive ectopic liver accessory to augment liver-specific functions as well as potentially treat various pathologies associated with compromised functions of liver, such as hemophilia B or alpha-1 antitrypsin deficiency. Abstract : The authors investigate the therapeutic potential of a vascularizable dual compartment hydrogel system for primary hepatocytes subcutaneous implantation in a mouse model. It is demonstrated that such a cell transplant device can be used as a minimally invasive ectopic liver accessory for improving the function. Supplemental digital content is available in the text.